Improving Student Vocabulary Mastery Through The Pictionary Words Game in Fifth Grade of Madrasah Ibtidaiyah Tarbiyatul Athfal Sumurber - Mohammad Tahmit; Novatrisna Dwi Nastiti (Kontribusia : Research Dissemination for Community Development, 2019)
This study aims to improve the ability of vocabulary in english through the implementation of pictionary words game in elementary school. Basically learning in the classroom must be done in a fun, but the teacher still do not know what techniques are able to attract student learning interest. In addition pictionary words game is also able to make all students active during the learning process. The author conducted a series of processes to identify problems that are happening. From interviews and observationS it can be concluded that the pictionary words game is quite effective in helping students remember vocabularies in English language